Effects of Road Construction in Nepal - Acharya, Krishna Raj (Tribhuvan University Journal, 2021)
It is widely accepted fact that rural roads have the most significant role in poverty reduction as they provide physical access to the rural population. Without the physical access, the rural population is being deprived from obtaining different services like health, education, drinking water, etc. In addition, lack of link between the rural areas and the market also creates the constraints on agricultural production and other economic activities. There is the knowledge gap as how the rural people can be benefited from the rural roads and what economic advantages are accessible from it. Thus this study is an attempt to explore how rural road helps in the creation of employment opportunities, reduction of input costs, increase in production and decrease in wastage and provide access to market and helps in poverty reduction. This study reveals that the rural road in the study area has significant impact on poverty reduction. From F-test, T-test, correlation as well as regression statistical analysis, it was concluded that there is significant relation of increase in income, reduction in time to market, occupation, and number of working age family members with the increase in savings. It can be claimed that this study has met its objectives of studying the impacts of rural road in poverty reduction.